P695 Epidemiology of key STIs among female sex workers in the middle east and north africa: systematic review and meta-analytics. (14th July 2019) - Chemaitelly, Hiam; Weiss, Helen; Smolak, Alex; Majed, Elzahraa; Abu-Raddad, Laith
Abstract : Background: This study characterizes the epidemiology of Treponema pallidum (syphilis), Chlamydia trachomatis, Neisseria gonorrhoeae, Trichomonas vaginalis, and herpes simplex virus type 2 (HSV-2) among female sex workers (FSWs) in the Middle East and North Africa (MENA), a neglected research area. Methods: Literature was systematically reviewed, with findings reported following PRISMA guidelines. Pooled prevalences of current and/or lifetime infection for each STI were estimated using random-effects meta-analyses. Sources of between-study heterogeneity were determined through meta-regressions. Results: One T. pallidum incidence study and 144 STI prevalence studies were identified for 45, 812 FSWs in 13 MENA countries. Pooled prevalence of current infection was 12.7% (95% confidence interval-CI: 8.5–17.7%) for T. pallidum, 14.4% (95% CI: 8.2–22.0%) for C. trachomatis, 5.7% (95% CI: 3.5–8.4%) for N. gonorrhoeae, and 7.1% (95% CI: 4.3–10.5%) for T. vaginalis . Pooled prevalence of lifetime infection was 12.8% (95% CI: 9.4–16.6%) for T. pallidum, 80.3% (95% CI: 53.2–97.6%) for C. trachomatis, and 23.7% (95% CI: 10.2–40.4%) for HSV-2. The multivariable meta-regression for T. pallidum prevalence demonstrated strong subregional differences, with the Horn of Africa and North Africa showing, respectively, six-fold (adjusted odds ratio (AOR): 6.4; 95% CI: 2.5–16.8) and five-fold (AOR: 5.0; 95% CI: 2.4–10.6) higher odds for prevalence than Eastern MENA. There was also strong evidence for a declining T. pallidum prevalence at a rate of 7% per year (AOR: 0.93; 95% CI: 0.88–0.98). Study-specific factors including diagnostic method, sample size, sampling methodology, and response rate, were not associated with syphilis prevalence. Conclusion: STI infection levels among FSWs in MENA are considerable, supporting a key role for commercial heterosexual sex networks in transmission dynamics, and highlighting the health needs of this neglected and vulnerable population. Syphilis prevalence in FSWs appears to be declining for at least three decades. Gaps in evidence persist for multiple countries. Disclosure: No significant relationships.